Instructional Leadership Paradigms and Faculty Performance in a Private Philippine Higher Education Institution - Payos, John Paul; Cera, Pauline Grace; Rosales, Mary Catherine; Cruz, Vienna; Fajilan, Daniel; Bogador, Dhurie; Pangilinan, Rosalina (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the instructional leadership paradigms practiced by academic administrators at Asia Technological School of Science and Arts (ASIATECH) and determined their relationship with faculty performance in a private higher education institution. The study was anchored on the Instructional Leadership Model of Hallinger and Murphy and the Multifactor Leadership Theory of Bass and Avolio. Using a descriptive-correlational quantitative research design, data were gathered from 106 actively teaching faculty members through total enumeration. A researcher-made questionnaire adapted from the Principal Instructional Management Rating Scale (PIMRS) was used to assess instructional leadership, while official faculty performance evaluation records from the Human Resource Office served as the measure of faculty performance. Descriptive and inferential statistics, including weighted mean, standard deviation, Pearson product-moment correlation, and one-way analysis of variance, were employed to analyze the data. Findings revealed that academic administrators demonstrated a high level of instructional leadership, with managing the instructional program receiving the highest rating. Faculty performance was rated very satisfactory, with instructional competence emerging as the strongest performance dimension, while research and extension obtained comparatively lower ratings. A very strong and statistically significant positive relationship was found between instructional leadership and faculty performance, indicating that stronger instructional leadership is associated with improved faculty outcomes. No significant difference was observed in instructional leadership perceptions between full-time and part-time faculty members. The study concludes that effective instructional leadership contributes to enhanced faculty performance and institutional quality. It recommends strengthening leadership development programs, implementing structured instructional supervision, expanding faculty research support, promoting inclusive professional development initiatives, and conducting broader multi-institutional and longitudinal studies. This study supports Sustainable Development Goal (SDG) 4: Quality Education by promoting effective instructional leadership and improved teaching quality, and SDG 8: Decent Work and Economic Growth through faculty professional development and effective educational leadership. Its sustainability impact lies in providing evidence that informs institutional leadership, quality assurance, and continuous improvement initiatives that strengthen long-term academic excellence in higher education.